To solve for x you can first divide by 12 into both sides of the equation, like this
![\begin{gathered} (12\mleft(x-2.3\mright))/(12)=(15.6)/(12) \\ x-2.3=1.3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/nl9lupkupfxlsu790bw3311cp4yf29nmsr.png)
Now, you can add 2.3 from both sides of the equation
![\begin{gathered} x-2.3+2.3=1.3+2.3 \\ x=3.6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3ta6iqs74aaxsoxa365e1464omt4gbb2d2.png)
Therefore, the value of x that satisfies the equation is
![x=3.6](https://img.qammunity.org/2023/formulas/mathematics/college/pkhpdy4nakk10k74ci6rwrs6dlcog4aibk.png)
Finally, to check that this value satisfies the given equation, just plug x = 3.6 into the equation and see that a true proposition is reached. So, you have
![\begin{gathered} 12\mleft(x-2.3\mright)=15.6 \\ \text{ Replace x = 3.6} \\ 12(3.6-2.3)=15.6 \\ 12(1.3)=15.6 \\ 15.6=15.6 \\ \text{ True proposition} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/id23ghj1iol1f1e1tkbbfhnsgp4ffrogv9.png)